Leading Digital Transformation: Principal Strategies for Building a Digital School Culture - Dwi Andini; Maya Novita Sari (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aimed to analyze the principal’s leadership in developing a digital school culture by examining leadership strategies, implementation processes, and challenges in integrating technology within the school environment. A qualitative approach with a case study design was employed. Participants included the principal, teachers, and educational staff selected through purposive sampling. Data were collected through semi-structured interviews, classroom and school observations, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings revealed that the principal enacted visionary, transformational, and adaptive leadership by integrating technology-driven initiatives with Islamic values to promote a sustainable digital school culture. Leadership practices were reflected in the implementation of digital policies, continuous teacher professional development, and the integration of digital technologies into teaching and learning activities. These strategies enhanced teachers’ digital competence, strengthened collaborative practices, and increased student engagement in technology-supported learning. Nevertheless, several challenges persisted, including inadequate technological infrastructure, unstable internet connectivity, and the potential misuse of digital technologies by students. This study demonstrates that effective digital school transformation depends not only on technological resources but also on strong, adaptive, and values-based school leadership. The findings contribute to the digital leadership literature by highlighting the importance of aligning technological innovation, organizational culture, and institutional values to foster sustainable digital school development.